Extensive monitoring of the natural menstrual cycle using the serum biomarkers estradiol, luteinizing hormone and progesterone - Anckaert, Ellen (Pract Lab Med, 2021)
Expected values for estradiol (E2), luteinizing hormone (LH), and progesterone determined in serum allow accurate assessment of menstrual cycle phase. Automated immunoassays demonstrate variable degrees of bias, emphasizing the need to establish method-specific reference values. We therefore established method-specific reference intervals for the Elecsys® LH assay and new generation Elecsys Estradiol III and Progesterone III assays (cobas e 801 analyzer) in 85 apparently healthy women aged 22–37 (US)/18–37 (EU) years over one natural menstrual cycle. Cycle length and day of ovulation were standardized; phases were defined by LH surge and/or progesterone/E2 levels. Median (5th–95th percentile) concentrations (follicular/ovulation/luteal) were E2: 198 ​pmol/L (114–332), 757 ​pmol/L (222–1959) and 412 ​pmol/L (222–854); LH: 7.14 IU/L (4.78–13.2), 22.6 IU/L (8.11–72.7) and 6.24 IU/L (2.73–13.1); progesterone: 0.212 ​nmol/L (0.159–0.616), 1.81 ​nmol/L (0.175–13.2) and 28.8 ​nmol/L (13.1–46.3). Sub-phase (early/intermediate/late) reference values were also determined for follicular and luteal phases. This multicenter study established reliable, method-specific E2, LH and progesterone reference values that could assist clinical decision-making in women with fertility disorders and monitoring of natural cycles in assisted reproductive treatment.